mRNA Relative Expression Catalase in Hypertension - Yohana, Yohana; Faradilla, Meutia Atika; Meiyanti, Meiyanti; Hartanti, Monica Dwi; Margo, Eveline; Anastasya, Karina Shasri (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Hypertension is number one worldwide disease which lead to death. Initially hypertension is caused by changes in the walls of blood vessels. These vascular changes are due to the accumulation of ROS (Reactive Oxygen Species). ROS is the result of the balance between antioxidants and oxidants, but uncontrolled conditions will cause vascular damage. One of ROS product from metabolism which could played role in downregulation antioxidant gene expression is hydrogen peroxide. Hydrogen peroxide could be neutralized by catalase enzyme. Studies about catalase expression in hypertension subject is still limited. This research aims to determine mRNA relative expression catalase in hypertension. In this case control study, thrity subject hypertension and normotension subject were recruited within the age of 50-60 years. Hypertension subject was chosen according to JNC 8. Two millilitres vein blood was isolated into RNA. mRNA expression was detected by qRT PCR with 2 steps. Relative expression was determined using livak method. The data was analyzed using Mann Withney test with GraphPad software. Research results show that (1) catalase mRNA relative expression was 0,6 fold in hypertension; (2) catalase relative expression was not significantly lower in hypertension; (3) other antioxidants might have other mechanism to detoxify ROS and prevent hypertension.